Evangelical faith and the challenge of historical criticism - Hays, Christopher M. (United States of America Baker Academic, 2013)
Many introductions to biblical studies describe critical approaches, but they do not discuss the theological implications. This timely resource discusses the relationship between historical criticism and Christian theology to encourage evangelical engagement with historical-critical scholarship. Charting a middle course between wholesale rejection and unreflective embrace, the book introduces evangelicals to a way of understanding and using historical-critical scholarship that doesn't compromise Christian orthodoxy. The book covers eight of the most hotly contested areas of debate in biblical studies, helping readers work out how to square historical criticism with their beliefs. -- Publisher a Towards a faithful criticism / Christopher M. Hays -- Adam and the fall / Christopher M. Hays and Stephen Lane Herring -- The exodus: fact, fiction or both? / Christopher B. Ansberry -- No covenant before the exile? : the Deuteronomic Torah and Israel's covenant theology / Christopher B. Ansberry and Jerry Hwang -- Problems with prophecy / Amber Warhurst, Seth B. Tarrer and Christopher M. Hays -- Pseudepigraphy and the canon / Christopher B. Ansberry, Casey A. Strine, Edward W. Klink III and David Lincicum -- The historical Jesus / Michael J. Daling and Christopher M. Hays -- The Paul of Acts and the Paul of the epistles / Aaron J. Kuecker and Kelly D. Liebengood / Faithful criticism and a critical faith / Christopher B. Ansberry and Christopher M. Hays.
a Towards a faithful criticism / Christopher M. Hays -- Adam and the fall / Christopher M. Hays and Stephen Lane Herring -- The exodus: fact, fiction or both? / Christopher B. Ansberry -- No covenant before the exile? : the Deuteronomic Torah and Israel's covenant theology / Christopher B. Ansberry and Jerry Hwang -- Problems with prophecy / Amber Warhurst, Seth B. Tarrer and Christopher M. Hays -- Pseudepigraphy and the canon / Christopher B. Ansberry, Casey A. Strine, Edward W. Klink III and David Lincicum -- The historical Jesus / Michael J. Daling and Christopher M. Hays -- The Paul of Acts and the Paul of the epistles / Aaron J. Kuecker and Kelly D. Liebengood / Faithful criticism and a critical faith / Christopher B. Ansberry and Christopher M. Hays.
Keywords: Evangelicalism; Christianity